2007
DOI: 10.1002/hep.21593
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent hypoxia predisposes to liver injury

Abstract: Obstructive sleep apnea (OSA) is characterized by chronic intermittent hypoxia (CIH). OSA is associated with nonalcoholic steatohepatitis (NASH) in obese subjects. The aim of this study was to investigate the effects of CIH on the liver in the absence of obesity. Lean C57BL/6J mice (n ‫؍‬ 15) on a regular chow diet were exposed to CIH for 12 weeks and compared with pair-fed mice exposed to intermittent air (IA, n ‫؍‬ 15). CIH caused liver injury with an increase in serum ALT (224 ؎ 39 U/l versus 118 ؎ 22 U/l i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
187
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(204 citation statements)
references
References 47 publications
12
187
1
2
Order By: Relevance
“…We hypothesize that severe obesity per se acts as ''the first hit'' in the progression of NAFLD inducing hepatic steatosis, whereas the presence of CIH of OSA acts as the ''second hit'' (21), inducing progression of hepatic steatosis to NASH. Our previous experiments in the mouse model showed that CIH increases lipid peroxidation and activates a redox-dependent transcription factor, NF-kB, in the liver (44,45). We have also shown that, in mice with diet-induced hepatic steatosis, but not in mice with normal livers, CIH increases liver levels of proinflammatory cytokines IL-1b, IL-6, macrophage inflammatory protein-2, and tumor necrosis factor-a as well as a1(I) collagen and indices of lobular inflammation and fibrosis (27,45,46).…”
Section: Osa and Nash In Severe Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that severe obesity per se acts as ''the first hit'' in the progression of NAFLD inducing hepatic steatosis, whereas the presence of CIH of OSA acts as the ''second hit'' (21), inducing progression of hepatic steatosis to NASH. Our previous experiments in the mouse model showed that CIH increases lipid peroxidation and activates a redox-dependent transcription factor, NF-kB, in the liver (44,45). We have also shown that, in mice with diet-induced hepatic steatosis, but not in mice with normal livers, CIH increases liver levels of proinflammatory cytokines IL-1b, IL-6, macrophage inflammatory protein-2, and tumor necrosis factor-a as well as a1(I) collagen and indices of lobular inflammation and fibrosis (27,45,46).…”
Section: Osa and Nash In Severe Obesitymentioning
confidence: 99%
“…Our previous experiments in the mouse model showed that CIH increases lipid peroxidation and activates a redox-dependent transcription factor, NF-kB, in the liver (44,45). We have also shown that, in mice with diet-induced hepatic steatosis, but not in mice with normal livers, CIH increases liver levels of proinflammatory cytokines IL-1b, IL-6, macrophage inflammatory protein-2, and tumor necrosis factor-a as well as a1(I) collagen and indices of lobular inflammation and fibrosis (27,45,46). Our present report and previous experimental data suggest that the hypoxic stress of OSA may induce oxidative stress in the livers of patients with severe obesity, leading to inflammation and fibrosis, which culminate in NASH.…”
Section: Osa and Nash In Severe Obesitymentioning
confidence: 99%
“…In hypoxia, serum cholesterol and LDL levels in mice fed creatine supplementation were lower compared to the control birds fed normal diet (Savransky et al 2007). High basal cholesterol levels and reduced blood total cholesterol have been observed in human males and females fed supplemental creatine (Earnest et al 1996).…”
Section: Blood Biochemical and Haematological Parametersmentioning
confidence: 96%
“…Several studies have considered the mechanism of facilitated glycogen accumulation of OCCC (12,13), but a conclusion has not yet been reached. Some studies have found that the glycogen accumulation in several kinds of tumor cells was accelerated under hypoxic conditions (14)(15)(16)(17)(18). Under such a hypoxic environment, hypoxia-inducible factor 1 (HIF1) is expressed and functions as the main factor regulating the metabolism of the cell (19).…”
Section: Introductionmentioning
confidence: 99%